Acute Stroke or Transient Ischemic Attack Treated with Aspirin or Ticagrelor and Patient Outcomes (SOCRATES) trial: rationale and design. Issue 8 (26th August 2015) - Johnston, S. Claiborne; Amarenco, Pierre; Albers, Gregory W.; Denison, Hans; Easton, J. Donald; Held, Peter; Jonasson, Jenny; Minematsu, Kazuo; Molina, Carlos A.; Wong, Lawrence K. S.
Abstract : Rationale: The risk of recurrent ischemia is high in the acute period after ischemic stroke and transient ischemic attack. Aspirin is recommended by guidelines for this indication, but more intensive antiplatelet therapy may be justified. Aims: We aim to evaluate whether ticagrelor, a potent antiplatelet agent that blocks the P2Y12 receptor without requiring metabolic activation, reduces the risk of major vascular events compared with aspirin when randomization occurs within 24 h after symptom onset of a nonsevere ischemic stroke or high‐risk transient ischemic attack. Design: Acute Stroke or Transient Ischemic Attack Treated with Aspirin or Ticagrelor and Patient Outcomes (SOCRATES) is a randomized, double‐blind, event‐driven trial and will include an estimated 13 600 participants randomized in 33 countries worldwide to collect 844 primary events. Study outcomes: The primary endpoint is the composite of stroke (ischemic or hemorrhagic), myocardial infarction, and death. Time to the first primary endpoint will be compared in the treatment groups during 90‐day follow‐up, with major hemorrhage serving as the primary safety endpoint. Participants will be followed for an additional 30 days after the randomized treatment period. Discussion: The SOCRATES trial fulfills an important clinical need by evaluating a potent antiplatelet agent as a superior alternative to current standard of care in patients presenting acutely with ischemic stroke or transient ischemic attack.